Local Vino : The Winery Boom in the Heartland - Pennell, James R. (Book collections on Project MUSE., 2016)
The art and craft of winemaking has put down roots in Middle America, where enterprising vintners coax reds and whites from the prairie earth while their businesses stand at the hub of a new tradition of community and conviviality. James R. Pennell tracks among the hardy vines and heartland terroir of wineries across Illinois, Iowa, Indiana, and Ohio. Blending history and observation, Pennell gives us a ground-up view of the business from cuttings and cultivation to sales and marketing. He also invites entrepreneurs to share stories of their ambitions, hard work, and strategies. Together, author and subjects trace the hows and whys of progress toward that noblest of goals: a great vintage that puts their winery on the map.